Netzwerke des Wissens - Thematische und personelle Relationen innerhalb der halleschen Zeitungen und Zeitschriften der Aufklärungsepoche (1688-1818) - Purschwitz, Anne (Journal of Historical Network Research, 2018)
Given that the amount of available digital sources is constantly growing, studies on the acquisition and transmission of knowledge in the public sphere tend to be methodologically selective in their analysis of historical discourses. These studies, as a rule, tend to offer a very partial image from an intellectual history perspective of the production, representation, reception, and evaluation of knowledge. A more productive approach would be to analyse the ways in which pre-modern knowledge production functioned based on the broadest possible sample of sources. The project will seek, with a computer-based methodology, to consistently compile and systematically analyse all 356 journals and periodicals published in Halle between 1688 and 1815, as well as to gather information on all the actors participating in the process (authors, editors, printers et cetera). The periodical press of the Enlightenment is particularly relevant for this type of approach. Newspapers and periodicals allowed for a broader circulation of the ideas of the educated and for faster reactions to news, controversies, and publications, as they became a widely accepted form of interpersonal communication. They thus filled a public and institutional gap and provided an open and adaptable medium for various public discourses without thematic limitations. We qualitatively go beyond standard discourse analysis by using a wealth of text and network data digitally available to reconstruct the breadth and depth of all the types of discourses of the Enlightenment, the combined quantitative methods for text and network analysis will allow us to trace the impact of the many involved parties right into the structure of the discourses.